(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
Effective oral presentation skills are essential for success in academic and professional settings. They enable students and researchers to communicate ideas clearly, persuasively, and confidently. This paper explores the significance of oral presentation skills in academic contexts, examines the key components of successful presentations, and provides strategies for improvement. The study highlights the importance of language proficiency, body language, organization, and audience awareness. Moreover, it emphasizes the role of technology and practice in developing these skills. The findings suggest that systematic training and continuous feedback can significantly enhance learners’ academic communication competence.